2018
DOI: 10.1016/j.applthermaleng.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanoparticle morphology and its dispersion ability regarding thermal properties of water used as phase change material

Abstract: Nanoparticles with different morphologies were added to water to study if the morphology of the nanoparticles affects the main parameters of water used as phase change material (PCM). Considered morphologies were spherical, tubes and sheets in the form of spherical carbon black nanoparticles (CB), multiwalled carbon nanotubes (MWCNT), and graphene oxide nanosheets (GO). Results demonstrate that effectively the morphology of nanoparticles affect the thermophysical properties of the nano-enhanced PCM (NePCM). De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Wang et al 127 added 1 wt % copper nanoparticles to the water-based PCM and found that the subcooling of the PCM was reduced by 20.5%, and the total cooling time was reduced by 19.2%. Camila et al 128 added spherical carbon black nanoparticles, CNTs, and graphene oxide nanosheets to PCMs and found that nanoparticles can reduce the supercooling of the material. Among them, spherical carbon black nanoparticles have the greatest effect on the undercooling of the PCM, which can reduce the undercooling at 5 °C.…”
Section: Role Of Additives and Comparativementioning
confidence: 99%
“…Wang et al 127 added 1 wt % copper nanoparticles to the water-based PCM and found that the subcooling of the PCM was reduced by 20.5%, and the total cooling time was reduced by 19.2%. Camila et al 128 added spherical carbon black nanoparticles, CNTs, and graphene oxide nanosheets to PCMs and found that nanoparticles can reduce the supercooling of the material. Among them, spherical carbon black nanoparticles have the greatest effect on the undercooling of the PCM, which can reduce the undercooling at 5 °C.…”
Section: Role Of Additives and Comparativementioning
confidence: 99%
“…This could be as a result of the differences in diffusion rates of the material change with the aspect ratio of the material (e.g., higher drag on a tubular structure compared to a perfect sphere) or because of steric hindrance in the collisions as the morphology limits inter-particular interactions [43]. Several reports have addressed the role of shape and size on cellular internalization [44][45][46].…”
Section: Particle Morphologymentioning
confidence: 99%
“…Carbon materials have good photo absorption capability and high thermal conductivity, which are excellent supporting additives to fabricate composite PCMs for solar thermal energy storage . Many kinds of carbon materials have been composited with PCMs to overcome the shortcomings for solar thermal energy storage, such as carbon nanotubes (CNTs), , graphene oxide (GO), carbon black, , and graphite. , Several research studies have reported that the thermal properties of paraffin can be improved by adding carbon materials. Zhang et al developed a composite PCM by adding multi-walled CNTs as-modified by acid oxidation.…”
Section: Introductionmentioning
confidence: 99%